Parallel Computations with Large-scale Air Pollution Models - Dimov, I.; Farago, I.; Zlatev, Z. (Інститут програмних систем НАН України, 2003)
Large-scale mathematical models are very powerful tools in the efforts to provide more
information and more detailed information about the pollution levels, especially about pollution levels which exceed certain critical values.. However, the model used must satisfy at least two conditions: (i) it must be verified that the model results are reliable and (ii) it should be possible to carry out different study by using the model. It is clear that comprehensive studies about relationships between different input parameters and the model results can only be carried out (a) if the numerical methods used in the model are sufficiently fast and (b) if the code runs efficiently on the available high-speed computers. Some results obtained recently by a new unified version of the Danish Eulerian Model will be presented in this paper. Великомасштабні математичні моделі – дуже потужний інструмент для одержання більш детальної інформації щодо рівнів забруднень. Проте використовувана модель повинна задовольнити принаймні двом умовам: (i) результати моделювання повинні бути надійними і
(ii) повинна існувати можливість уточнення і вивчення різноманітних характеристик моделей. Всебічне вивчення відношень між різноманітними параметрами входу і результатами моделювання може бути виконане, якщо (a) чисельні методи, використовувані в моделі, достатньо швидкі та (b) програмне забезпечення на доступних швидкодіючих
комп'ютерах достатньо ефективне. Подані результати рівнобіжної реалізації моделювання забруднення атмосфери, отримані в новій об'єднаній версії датської Ейлерової моделі. Крупномасштабные математические модели – очень мощный инструмент для получения более детальной информации относительно уровней загрязнений. Однако модель должна удовлетво-
рить по крайней мере двум условиям: (i) результаты моделирования должны быть надежными и (ii) должна существовать возможность уточнения и изучения характеристик модели. Всестороннее изучение отношений между различными параметрами входа и результатами моделирования может быть выполнено, если (a) численные методы, используемые в модели, достаточно быстры и (b) программное обеспечение на доступных быстродействующих компь-
ютерах достаточно эффективно. Представлены результаты параллельной реализации моделирования загрязнения атмосферы, полученные в новой объединенной версии датской Эйлеровой модели.